STUDY OF NARRATION ON SATYA BUDHI TEMPLE’S GATE IN BANDUNG - Fortino, Edbert Theo; Darmayanti, Tessa Eka (Universitas Telkom, 2023)
This article examines narratives in architectural forms to details of the ornaments and reliefs on the gate as one of the important components in a temple building because as it starts from the architectural form of the temple gate until the details of its ornaments and reliefs that engraved on its surface tells a story, meaning, and deep philosophy to its people. Satya Budhi Temple as one of the oldest temples in Bandung that has been established for more than 15 decades, which is around 157 years until it is designated as a heritage building type A becomes the object of research in this article as the temple building has a very high historical value. This study aims to narrate the meaning, story, and philosophy behind the architectural form of the gate to the details of its ornaments and reliefs that are engraved or drawn along the surface of the gate. This research method was carried out qualitatively using a case study approach with cultural and historical theory to study the components of architectural elements, to the meaning and story that is rooted through the reliefs and decorative ornaments at the gate. There is also a research instrument which is observation, and interview guidelines as the key instruments. The data source of this research is the result of interviews from the management of Satya Budhi Temple, Architects or researchers with specialization or expertise in heritage buildings or building with cultural elements, as well as the surrounding community. So that this research has an impact to find out the story and philosophical meaning that is implied through the form of Satya Budhi's temple gate components form. Keywords : Gate; Narration; Temple; Ornament; Philosophy